2021
DOI: 10.1111/ddg.14453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and mycological study of 42 cases of dermatophytic granuloma (Majocchi granuloma)

Abstract: Dermatophytes are keratinophilic fungi, which cause superficial mycoses that often remain limited to the stratum corneum. Local or general immunosuppressed environments predispose to deep tissue invasion and development of diseases such as Majocchi granuloma, dermatophytic granuloma (DG), deep dermatophytosis, disseminated dermatophytosis (Hadida's disease) and pseudomycetoma [1][2][3].Dermatophytic granuloma, also known as granulomatous nodular perifolliculitis, is the most frequent manifestation of dermatoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In 2018, a comprehensive review of published cases of MG from 1883 to 2017 revealed a total of 112 reported cases worldwide. 1 Since then, <20 additional cases have been reported in addition to 2 centers describing their cases of MG. 6 , 15 To date, our study is the single largest cohort of patients with MG in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a comprehensive review of published cases of MG from 1883 to 2017 revealed a total of 112 reported cases worldwide. 1 Since then, <20 additional cases have been reported in addition to 2 centers describing their cases of MG. 6 , 15 To date, our study is the single largest cohort of patients with MG in the literature.…”
Section: Discussionmentioning
confidence: 99%